“To feel him love me”: Emerging intersections of identity, queerness, and differing ability - Harvey, Rebecca (Gender, sex, and sexuality among contemporary youth, 2017)
AbstractOriginality/value This paper provides an alternative approach to nurturing queer identity by (1) creating refuge for emerging sexualities; (2) allowing for difficult dialogues where ability, sexuality, and gender can be pragmatically discussed, performed, and negotiated; (3) tolerating the discomfort of these difficult dialogues and pushing through to nurturing the unique queerness that evolves out of these conversations; and finally (4) encouraging transformation of all participants including client and practitioners. The practitioners discuss their own transformation through the co-created dialog with each other and with the client.
Keywords: Disability; Gay; Gay couple; Intersectionality; Queer; dept.mft; dept.swk

Indian perspectives on treating substance use disorders - Perumbilly, Sebastian A; Anderson, Stephen A (Alcoholism Treatment Quarterly, 2017)
Although research on substance use disorders (SUDs) largely focuses on the developed world, treatment programs from the developing world seldom get international attention. Focusing on India, this study was designed (1) to describe India’s treatment programs, and (2) to report Indian perspectives on critical factors related to treating SUDs. An online survey instrument was created, based on mixed-methods approach with concurrent strategies, to collect data. Participants were India’s clinicians (N = 112). Indian treatment approach suggests that SUDs must be treated by a multidisciplinary treatment team with a comprehensive plan that must include systemically focused clinical interventions in patients’/clients’ relevant relational systems. Findings may have relevance to clinicians, researchers, and policy makers globally. © 2017 Taylor & Francis.
Keywords: Addiction treatment; India; Indian; Note; adult; aged; clinical assessment; comparative study; controlled study; critical factors; dept.mft; drug dependence; family therapy; female; health survey; human; involving families; major clinical study; male; peer-reviewed; professional development; substance use disorders

Parents’ personal growth: expanding the view of therapy for child behavioral problems - Perumbilly, Sebastian A; Anderson, Stephen A; Boylin, William M (Journal of Family Psychotherapy, 2017)
Parenting literature often focuses on parental strategies that promote positive behavioral outcomes for children, but ignores key aspects of parents’ own growth process. This article presents a critical review of current literature on parenting and highlights the importance of focusing on parents’ growth in therapy. A clinical framework to define parents’ growth is offered along with case vignettes and practical guidelines for clinicians in order to assess parents’ growth. © 2017 Taylor & Francis Group, LLC.
Keywords: Article; Couple intimacy; behavior therapy; child behavior; child care; child parent relation; dept.mft; education program; family therapy; growth; human; intimacy; medical literature; parental attitude; parenting; parents’ growth; personal growth; personal needs; practice guideline; problem behavior; responsibility; self care; social isolation; training; vignette

Lesbian couples - Stone Fish, Linda; Harvey, Rebecca (Encyclopedia of couple and family therapy, 2017)
Keywords: Current Political Climate; Difficult Dialogue; Donor Insemination; LGBTQ Community; Lesbian Couple; dept.mft